JPTCP 2022
DOI: 10.47750/jptcp.2022.888
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of the Impaired Functions and Life Limitations of the Disabled People Due to the Coronary Heart Disease

Abstract: The article presents the characteristics of the impaired functions and life limitations of disabled individuals due to coronary heart disease, considering the clinical data, the disease stages, and the disability severity. It was revealed that the largest share in the structure of impaired functions was made up by the impaired functions of the cardiovascular neuromuscular, movement-related (statodynamic), endocrine systems and metabolism and life limitations of I, II and III degrees related to self-care, movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Taking modifiable (smoking, dietary, and exercise behaviors) and non-modifiable (ageing processes) risk factors together, the prevalence of chronic diseases increases with age [6]. The increasing incidence of chronic diseases, including cardiovascular, neurodegenerative, and metabolic diseases, is associated with a decline in functional ability of older adults [7][8][9]. Functional ability is defined as "having the capabilities that enable all people to be and do what they have reason to value" and includes basic activities of daily living (ADLs) such as dressing, toileting, and ambulating [10].…”
Section: Introductionmentioning
confidence: 99%
“…Taking modifiable (smoking, dietary, and exercise behaviors) and non-modifiable (ageing processes) risk factors together, the prevalence of chronic diseases increases with age [6]. The increasing incidence of chronic diseases, including cardiovascular, neurodegenerative, and metabolic diseases, is associated with a decline in functional ability of older adults [7][8][9]. Functional ability is defined as "having the capabilities that enable all people to be and do what they have reason to value" and includes basic activities of daily living (ADLs) such as dressing, toileting, and ambulating [10].…”
Section: Introductionmentioning
confidence: 99%
“…There are about 11 million patients with CHD in China, of which the mortality rate of CHD in urban residents is 126.91 per 100,000, and that of rural residents is 135.88 per 100,000 ( Su et al, 2023 ). CHD can also have detrimental effects on the nervous system, endocrine system, and mental health ( Shmakova et al, 2022 ). Epidemiological studies have found that nearly 31% of patients with CHD have anxiety and depression ( Palacios et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The current management mode of patients with CHD is medical management and hierarchical prevention ( Shmakova et al, 2022 ). The primary object of drug therapy is to alleviate symptoms of angina pectoris and reduce the occurrence of cardiovascular events.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the prevalence of CVDs has increased in recent decades. Numerous investigations have shown that the control of CVD risk factors, such as blood pressure, blood lipids, obesity, and blood sugar, could lead to the improvement of patients’ complications (Khunti et al, 2018; Randhawa et al, 2020; Shmakova et al, 2022).…”
Section: Introductionmentioning
confidence: 99%